The Influence of Locus of Control and Work Environment on the Performance of Lau Sub-District Office Employees, Maros Regency - Amir, Ridwan; Nur, Kherayani; Hamka (PT. Global World Scientific, 2023)
The objectives to be achieved in this research are (1) To determine the effect of locus of control on the performance of employees at the Lau sub-district office, Maros Regency, (2) To determine the work environment on the performance of employees at the Lau sub-district office, Maros Regency, and (3) To determine the influence of locus. of control and work environment together on the performance of employees of the Lau sub-district office, Maros district. The analytical method used in this research is quantitative descriptive to answer the hypothesis in this research. In answering the hypothesis, the instrument test method is used consisting of validity and reliability tests, prerequisite tests consist of normality, multicollinearity and heteroscedasticity tests, inferential tests consist of regression tests consisting of multiple linear regression analysis, correlation coefficient, coefficient of determination and hypothesis testing (partial test). and simultaneous). The results of the regression research Y= 1, 238 + 0.341 %. Then the remainder was influenced by other factors outside this research, amounting to 45.9%. The test results consist of (1) Hypothesis table 2.03951 with a significant value showing 0.000 < Sig 0.05, then the conclusion is that hypothesis that the hypothesis is proven, namely that locus of control and the work environment have a significant effect on the performance of employees at the Lau Subdistrict Office, Maros Regency.